Mengoptimalkan Kinerja Karyawan Melalui Kepemimpinan Transformasional, Budaya Organisasi dan Pengembangan Karir - Sabri; Susanto, Agus; Sari Lubis, Anggi (Bahtera Inovasi, 2025)
Amidst the dynamic and intense global manufacturing industry competition in Batam, high-performing human resources are a primary strategic asset for organizational sustainability. This study aims to analyze the influence of transformational leadership, organizational culture, and career development as crucial factors in optimizing employee performance. The object of this study is PT. Satnusa Persada Tbk, a leading electronics company in Batam. This research employs a quantitative approach with an explanatory research type. Data collection was conducted through the distribution of questionnaires to [Insert Sample Size] employees who served as research respondents. The collected data were analyzed using the Structural Equation Modeling (SEM) method with AMOS software. The results indicate that transformational leadership, organizational culture, and career development partially have a positive and significant influence on employee performance. These findings imply that to achieve optimal performance sustainably, company management needs to implement an integrative approach that combines inspirational leadership styles, the internalization of strong cultural values, and the provision of clear career development paths for its employees